Peran Guru Dalam Meningkatkan Kecerdasan Interpersonal Anak Usia Dini Melalui Kegiatan Pretend Play - Karim, Abdul; Fiorentisa, Iklila Febrianti (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2021)
Interpersonal intelligence is the intelligence possessed by individuals to establish relationships with others and maintain social interactions. The objectives of this study are (1) to describe the teacher's role as an educator in improving interpersonal intelligence through pretend play activities for B1 grade students at TK Muslimat NU 65 Wuluhan Jember (2) to describe the teacher's role as a facilitator in improving interpersonal intelligence through pretend play activities for participants. B1 grade students at Muslimat NU 65 Wuluhan Jember Kindergarten (3) Describe the teacher's role as a model in improving interpersonal intelligence through pretend play activities for B1 grade students at Muslimat NU 65 Wuluhan Jember Kindergarten. This research uses a qualitative research approach with the type of case study research. The data collection techniques used by researchers are: interview techniques, observation and documentation. Data analysis in this research is data condensation, data presentation, and conclusion drawing. While the validity of the data using source triangulation and method triangulation. The results of this study indicate: (1) The role of the teacher as a model educator in improving interpersonal intelligence through pretend play activities at TK Muslimat NU 65 Wuluhan Jember, namely (a) directly demonstrating the role that will be played by each child (b) providing examples of speech and movements that must be done by children when playing their role (c) provide examples of how to use supporting equipment for pretend play activities. in improving interpersonal intelligence through pretend play activities at TK Muslimat NU 65 Wuluhan Jember, namely (a) providing material explanations about pretend play (b) providing strengthening pretend play material (c) improving pretend play material with practice. (2) The role of the teacher as a facilitator in improving interpersonal intelligence through pretend play activities at TK Muslimat NU 65 Wuluhan Jember, namely (a) the teacher prepares tools according to the pretend play theme (b) chooses the right tool for pretend play material (c) helps children understand their role (d) provide assistance during pretend play activities (3) The role of the teacher as a model in improving interpersonal intelligence through pretend play activities at TK Muslimat NU 65 Wuluhan Jember, namely (a) directly demonstrate the role that will be played by each child (b) provide examples of speech and movements that must be done by children when playing their roles (c) provide examples of how to use supporting equipment for pretend play activities. Abstrak Kecerdasan interpersonal adalah kecerdasan yang dimiliki individu untuk menjalin hubungan dengan orang lain serta mempertahankan interaksi sosialnya. Tujuan penelitian ini adalah (1) Mendeskripsikan peran guru sebagai pendidik dalam meningkatkan kecerdasan interpersonal melalui kegiatan pretend play pada peserta didik kelas B1 di TK Muslimat NU 65 Wuluhan Jember (2) Mendeskripsikan peran guru sebagai fasilitator dalam meningkatkan kecerdasan interpersonal melalui kegiatan pretend play pada peserta didik kelas B1 di TK Muslimat NU 65 Wuluhan Jember (3) Mendeskripsikan peran guru sebagai model dalam meningkatkan kecerdasan interpersonal melalui kegiatan pretend play pada peserta didik kelas B1 di TK Muslimat NU 65 Wuluhan Jember. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan jenis penelitian studi kasus. Adapun teknik pengumpulan data yang digunakan oleh peneliti yaitu: teknik wawancara, observasi dan dokumentasi. Analisis data dalam penelitian ini yaitu kondensasi data, penyajian data, dan penarikan kesimpulan. Sedangkan keabsahan datanya menggunakan triangulasi sumber dan triangulasi metode. Hasil penelitian ini menunjukkan: (1) Peran guru sebagai pendidik model dalam meningkatkan kecerdasan interpersonal melalui kegiatan pretend play di TK Muslimat NU 65 Wuluhan Jember yaitu (a) mendemonstrasikan secara langsung peran yang akan dimainkan oleh setiap anak (b) memberikan contoh ucapan dan gerakan yang harus dilakukan oleh anak saat memainkan perannya (c) memberikan contoh cara menggunakan peralatan penunjang kegiatan pretend play. dalam meningkatkan kecerdasan interpersonal melalui kegiatan pretend play di TK Muslimat NU 65 Wuluhan Jember yaitu (a) memberikan penjelasan materi tentang pretend play (b) memberikan penguatan materi pretend play (c) menyempurnakan materi pretend play dengan praktik. (2) Peran guru sebagai fasilitator dalam meningkatkan kecerdasan interpersonal melalui kegiatan pretend play di TK Muslimat NU 65 Wuluhan Jember yaitu (a) guru menyiapkan alat yang sesuai dengan tema pretend play (b) memilih alat yang tepat untuk materi pretend play (c) membantu anak memahami peran mereka (d) melakukan pendampingan selama kegiatan pretend play berlangsung (3) Peran guru sebagai model dalam meningkatkan kecerdasan interpersonal melalui kegiatan pretend play di TK Muslimat NU 65 Wuluhan Jember yaitu (a) mendemonstrasikan secara langsung peran yang akan dimainkan oleh setiap anak (b) memberikan contoh ucapan dan gerakan yang harus dilakukan oleh anaksaat memainkan perannya (c) memberikan contoh cara menggunakan peralatan penunjang kegiatan pretend play.